Mode II interlaminar fracture toughness of CF/EP composite containing microencapsulated healing resins. (12th April 2017) - Ghazali, Habibah; Ye, Lin; Zhang, Ming Q.
Abstract: The effects of microcapsules containing healing resins on the Mode II interlaminar fracture toughness ( G IIC ) of carbon fibre/epoxy composite laminates were investigated using end-notched flexure (ENF) specimens. The results indicate that the Mode II interlaminar fracture toughness of the original CF/EP laminates was improved with the incorporation of a dual-component microencapsulated self-healant. It was observed that the microcapsules induced toughening via two mechanism: i) larger plastic deformation due to a thicker resin-rich interlaminar region and ii) microcapsules in tempering hackle formation. When subjected to healing after release of the microencapsulated resins, the dual-component healant provided the laminates with 63% healing efficiency in Mode II interlaminar fracture toughness. Observation of fracture surfaces using scanning electron microscopy also revealed that the healing efficiency varied directly with the concentration of healant and subsequently the formation of a dense interlaminar region after the original fracture.